2021
DOI: 10.1016/j.ajpath.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of β-Catenin/Forkhead Box Protein O Signaling Mediates Epithelial Repair in Kidney Injury

Abstract: Fibrosis is characterized by progressively excessive deposition of matrix components and may lead to organ failure. Transforming growth factor-b (TGF-b) is a key cytokine involved in tissue repair and fibrosis. TGF-b 0 s profibrotic signaling pathways converge at activation of b-catenin. b-Catenin is an important transcription cofactor whose function depends on its binding partner. Promoting b-catenin binding to forkhead box protein O (Foxo) via inhibition of its binding to T-cell factor (TCF) reduces kidney f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Studies from us and others demonstrated the key role for β-catenin/TCF in mediating profibrotic signaling of multiple pathways (Liu, 2010;Qiao et al, 2018). Importantly, we found that shifting β-catenin binding from TCF toward Foxo in both macrophages and kidney tubular cells by inhibition of β-catenin/TCF redirected TGFβ signaling from pro-fibrotic to anti-inflammatory, protected against kidney fibrosis and promoted epithelial repair in UUO and IRI models (Qiao et al, 2018;Rao et al, 2019Rao et al, , 2021Yang et al, 2019).…”
Section: Activation and Proliferation Of Myofibroblasts By Crosstalk Between Profibrotic Signaling Pathwaysmentioning
confidence: 50%
See 1 more Smart Citation
“…Studies from us and others demonstrated the key role for β-catenin/TCF in mediating profibrotic signaling of multiple pathways (Liu, 2010;Qiao et al, 2018). Importantly, we found that shifting β-catenin binding from TCF toward Foxo in both macrophages and kidney tubular cells by inhibition of β-catenin/TCF redirected TGFβ signaling from pro-fibrotic to anti-inflammatory, protected against kidney fibrosis and promoted epithelial repair in UUO and IRI models (Qiao et al, 2018;Rao et al, 2019Rao et al, , 2021Yang et al, 2019).…”
Section: Activation and Proliferation Of Myofibroblasts By Crosstalk Between Profibrotic Signaling Pathwaysmentioning
confidence: 50%
“…Kidney fibrosis is the direct result of activation of fibroblasts and accumulation of myofibroblasts, driven by multiple profibrotic signaling pathways (Kuppe et al, 2021). Profibrotic changes in other cells, including mesenchymal transition of tubular epithelial cells (EMT) (Zheng et al, 2009;Tan et al, 2010;Qiao et al, 2018;Yang et al, 2020;Rao et al, 2021) and endothelial cells (EndoMT) (Zeisberg et al, 2008;LeBleu et al, 2013;Zhao et al, 2016), also contribute to the activation of fibroblasts and kidney fibrosis, but may not directly transform into myofibroblasts (Kuppe et al, 2021).…”
Section: Macrophage Contribution To Profibrotic Signaling Pathwaysmentioning
confidence: 99%
“…The Fox signaling pathway plays an important role in the progression of organ fibrosis in chronic kidney disease ( 41 43 ). Targeting β-catenin/Foxo may reconstruct the normal structure of damaged kidneys, providing a novel therapeutic strategy for the treatment of organ failure in fibrotic diseases ( 44 , 45 ). Hypoxia inducible factor 1 (HIF1), a transcriptional complex, regulates cellular and systemic homeostatic responses to oxygen availability ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have demonstrated its involvement in the modulation of inflammatory processes and macrophage programming ( Ito et al, 2009 ; Yan et al, 2020 ; Ren J. et al, 2021 ). With respect to tissue healing, although some studies have linked FOXO1 to increased fibrosis under some pathological conditions ( Mori et al, 2014 ; Chung et al, 2019 ), studies have emphasised its positive roles, not only as an antifibrotic factor ( Xin et al, 2018 ; Huang et al, 2019 ) but also as a promoter for wound healing, via coordination with TGF-β signalling, enhancement of keratinocyte proliferation and wound epithelization and remodelling processes via the regulation of MMP/TIMP activities ( Ponugoti et al, 2013 ; Hameedaldeen et al, 2014 ; Zhang et al, 2017 ; Miao et al, 2019 ; Rao et al, 2021 ). Nonetheless, although the present study does not provide histological evidence of a similar or dissimilar pattern of tissue healing and regeneration between the two abutment types, the clinical evaluation did not reflect macroscopically superior healing at the electropolished abutment being associated with higher expression of FOXO1.…”
Section: Discussionmentioning
confidence: 99%